Response of qualitative characteristics of basil (Ocimum basilicum) plant to the biofertilizer EM1 and the effect of its extract on the growth of Aspergillus sp - نجاة إدريس عمر; مقبولة محمد حماد (African Journal of Advanced Pure and Applied Sciences, 2023)
This study examined the effect of four levels of EM1 biofertilizer (0, 1, 1.5, 2) ml. 1 liter of water as root nutrition (where the biofertilizer has been prepared previously) according to some qualitative characteristics for the basil plant. This study was conducted in the city of Al Bayda in 2023, and the results showed that There are significant differences between the concentrations of the biofertilizer, although the concentrations(1, 1.5, 2) ml/l, varied in their effect on the length of the plants, thus playing an important role in the characteristics. Quality: The rate of 2 ml/L gave the best results, and the radical addition method caused an increase in... The percentage of oil, improving the percentage of nitrogen and protein, and the plant extract of basil were also used in inhibiting the growth of Aspergillus spp fungi, it was found to have an inhibitory effect on this fungus.